Oxidation method affects radiocarbon analysis of natural solid samples: Implications for elemental analyzer vs. closed tube combustion - Seung-Cheol Lee; Gwan-Ho Lee; Hyunshin Koh; Eun-Ju Lee; Byung-Yong Yu; Jin Hur; Sunghwan Kim; Kyung-Hoon Shin; Neung-Hwan Oh (Marine Pollution Bulletin, 2026)

Abrupt decrease in vanadium in precipitation at two forested catchments in Japan associated with the IMO 2020 global sulfur regulation - Masayuki Morohashi; Hiroki Yotsuyanagi; Shiho Yabusaki; Ki-Cheol Shin; Toko Tanikawa; Naoyuki Yamashita; Junichi Kurokawa; Hiroyuki Sase (Atmospheric Environment, 2026)

Stochastic model predictive control for chiller systems using machine-learning models with quantified prediction uncertainty - Sunghyun Kim; Hansol Shin; Jeeye Mun; Joa Hyoung Lee; Yoonmee Doh; Cheol-Soo Park (Energy and Buildings, 2026)

Controlled fabrication and enhanced ultrafiltration performance of porous poly(m-phenylene isophthalamide) hollow fiber membranes via TiO2-assisted pore templating and selective removal - Gyeong-Ig Hwang; Ye-Rin Shin; Shinwoo Lee; Min-Young Hwang; Min-Cheol Kim; Sung-Hyuck Park; Won-Wook Lee; Young Gyu Jeong (Chemosphere, 2026)

Modulation of intestinal morphology and microbial ecosystem by Bacillus-based biotics and enzyme cocktails in broilers - Hae-Chan Shin; Seong-Min Koo; Jae-Hyeok Lee; Sang-Hyon Oh; Jae-Cheol Jang (Research in Veterinary Science, 2026)

Reusable composite adsorbent for aqueous solutions and soils multi-contaminated with As(V), Cd(II), Pb(II), and diesel - Jong Cheol Lee; Hailu Fu; Muhammad Kashif Irshad; Hun Ho Lee; Dong Hwan Shin; Sang Soo Lee (Journal of Water Process Engineering, 2026)

A new sintering mechanism, “silver-zipping”, for low-temperature sintering of oxide solid electrolytes - Dong-Hee Kim; Sehwa Cheon; Youngoh Kim; Suhyeon Lim; Doohun Kim; Sung Kang; Heon-Cheol Shin; Jun-Woo Park; Heetaek Park (Chemical Engineering Journal, 2026)

Protocol for in vitro differentiation of C2C12 myoblasts into mature myotubes - Jong Min Oh; Ji Hyo Lyu; Maic Audo Eybi Mayer Sihombing; Chang-Hwan Bae; Ung Cheol Shin; Subramanian Muthamil; Seon-Wook Kim; M. N. AZIM; Jong-Hoon Kim; Jun Hong Park (Molecular & Cellular Toxicology, 2026)

Compositional convergence of island demersal fish assemblages in the East Sea: a long-term trammel-net comparison between Dokdo and Ulleungdo - Seokjin Yoon; Ui Cheol Shin; Eunho Kim (Frontiers in Marine Science, 2026)
Marine fish assemblages are reorganizing under rapid ocean warming, yet long-term evidence for local compositional convergence between adjacent island systems remains scarce. Here we test whether neighboring island demersal fish assemblages in the East Sea have become more similar over two decades and whether this change is associated with a regional warming background. We analyzed shallow demersal fish assemblages around Dokdo and Ulleungdo using standardized, fishery-independent trammel-net surveys conducted at comparable bottom depths of approximately 50 m. Dokdo was monitored from 2006 to 2025, providing longer-term context, and Ulleungdo from 2013 to 2025; direct inter-island comparisons were restricted to the shared 2013–2025 period. Compositional change was quantified with Bray-Curtis dissimilarity, turnover-nestedness partitioning, ordination, and permutational analyses, with trends tested using rank correlation and autocorrelation-corrected Mann-Kendall tests. Both assemblages showed directional temporal reorganization. During the shared period, inter-island Bray-Curtis dissimilarity declined from 0.478 in 2013–2017 to 0.210 in 2021-2025, a decline driven by species turnover and robust to alternative dissimilarity metrics, raw biomass, dominant-species exclusion, leave-one-species-out tests, and temporal autocorrelation. Convergence coincided with a narrowing of the Ulleungdo-Dokdo gap in subtropical-affinity biomass, but species-level contributions showed that the pattern involved broad changes in taxa that formerly differentiated the two islands, not only warm-affinity species. Sea-surface temperature rose at similar rates around both islands and was a significant predictor of overall assemblage composition in generalized additive models, although direct causal attribution remained limited. Our results identify local biotic homogenization of adjacent island demersal fish assemblages under a regional warming background and highlight the value of standardized long-term surveys for detecting beta-diversity change in marine ecosystems.

Multispecies toxicity evaluation of extractable chemicals from commercial biodegradable plastic products - Soyeon An; Hwicheol Shin; In-Cheol Yeo; Chang-Bum Jeong; Dong-Ku Kang (Journal of Hazardous Materials, 2026)

Molybdenum-incorporated zinc phosphate hydrate nanorods for enhanced electrochemical performance in potassium-ion capacitors - Sonali A. Beknalkar; Jonghwan Park; Sagar M. Mane; Vinayak V. Satale; Pritam J. Morankar; Rutuja U. Amate; Jae Cheol Shin; Aviraj M. Teli (Chemical Engineering Journal, 2026)

ROMP-derived polymer binders with stepwise and facile multifunctionalization for high-performance silicon anode Li-ion batteries - Cheol Shin; Ji Young Kim; Gyuri Kim; Hansu Kim; In Hwan Jung (Chemical Engineering Journal, 2026)

MnO2-Pd integrated into NbP2O7 electrodes for hybrid supercapacitors - Aviraj M. Teli; Sonali A. Beknalkar; Vinayak V. Satale; Rutuja U. Amate; Pritam J. Morankar; Muhammad Asghar Khan; Manesh A. Yewale; Seong-ho Baek; Jae Cheol Shin (Chemical Engineering Journal, 2026)

Exposure to traffic-related air pollution and the risk of premature rupture of membranes: a cohort analysis of the Korean CHildren’s ENvironmental health Study (Ko-CHENS) - Dong-Wook Lee; Kyung A. Lee; Jongmin Oh; Hwan-Cheol Kim; Sanghwan Song; Yun-Chul Hong; Eunhee Ha; Suejin Kim; Choonghee Park; Sanghwan Song; Jueun Lee; Huibyeol Park; et al. (Environmental Science and Pollution Research, 2026)

Exosomal microRNA profiling reveals candidate biomarkers and regulatory signatures associated with paratuberculosis disease status in goats - Eun-Yeong Bok; Tae Yoon Kim; Sang-Young Seo; Han-Gyu Lee; Young-Hun Jung; Seong Hwan Bae; Nam Su Oh; Tae Jin Cho; Hyeon Woo Park; Eui Cheol Shin; Jae Kyeom Kim (The Veterinary Journal, 2026)

Nanomaterial-integrated laser-induced graphene electrochemical sensors for environmental pollutant detection - Ramalingam Manikandan; Jinyong Park; Hyeon-Geun Jang; Uma Aruljothi Mugunthan; Chang-Seok Kim; Bo-Sung Shin; Jang-Hee Yoon; Seung-Cheol Chang (Journal of Environmental Chemical Engineering, 2026)

Comprehensive analysis of cytokines as predictors of multi-organ dysfunction syndrome in patients with trauma: a prospective observational study - In Sik Shin; Myoung Jun Kim; Md Habibur Rahman; Cheol-Su Kim; Kwangmin Kim (Molecular & Cellular Toxicology, 2026)

Myosin light chain kinase 2 and Myomesin 2 are related to the stiffness of vocal fold lamina propria in aging rats and humans - Ji-Min Kim; Hyoung-Sam Heo; Hyoun-Wook Lee; Gi-Cheol Park; Sung-Chan Shin; Yong-il Cheon; Ha-Nee Kwon; Byung-Joo Lee (Biogerontology, 2026)

Biocontrol potential of beauvericin produced in a submerged culture of Beauveria bassiana 331R against cotton aphid Aphis gossypii - Jong-Cheol Kim; In Min Hwang; Ho Myeong Kim; Seulbi Kim; Hyunbok Song; Seulki Kim; Tae Young Shin; Taek Su Shin; Soo‑Dong Woo; Hae Woong Park (BioControl, 2026)

Low-Molecular-Weight Collagen Peptides Improve Hair Health in Adults with Damaged Hair: A Randomized, Double-Blind, Placebo-Controlled Trial - Yu-ri Gwon; AReum Kim; Mi Hye Seo; Ji-Hae Lee; Jin Hee Shin; Hae Kwang Lee; Byung Cheol Park; Joon Seok; Beom Joon Kim; Jinhak Kim; Miyoung Park (International Journal of Peptide Research and Therapeutics, 2026)

Associations of pre- and postnatal levels of three heavy metals with visual impairment in 3-year-old children - Dajeong Ham; Sung Yeon Kim; Sanghyuk Bae; Suejin Kim; Choonghee Park; Sanghwan Song; Jueun Lee; Huibyeol Park; JungHeum Jo; A-Ra Jung; Seung Do Yu; Hyun Jeong Kim; et al. (Environmental Research, 2025)

Effects of web-based behavioral intervention on fine particulate matter, pulmonary function, and airway inflammation in children: The COCOA randomized controlled trial - Dirga Kumar Lamichhane; Bo-Mee Kim; Jungyun Bae; Hea Young Oh; Dong In Suh; Youn Ho Shin; Kyung Won Kim; Kangmo Ahn; Hyo-Bin Kim; Song-I Yang; So-Yeon Lee; Soo-Jong Hong; et al. (Environmental Research, 2025)

Development and reproductive safety of AdCLD-CoV19, an adenoviral vector-based COVID-19 vaccine, in female Sprague–Dawley rats and their offspring - Sang-Jin Park; Seonghyeon Kim; Sangyun Kim; Kwang-Soo Shin; Chang-Yuil Kang; Eui-Ju Hong; Wan-Jung Im; Ji-Seong Jeong; Wook-Joon Yu; Kyong-Cheol Ko; Yong-Bum Kim (Toxicology and Applied Pharmacology, 2025)

Tuning liganded nanocrack geometry for dynamic regulation of host macrophages - Hyunsik Hong; Sungkyu Lee; Choongmo Kang; Jungyeon Rhi; Hwapyung Jung; Ramar Thangam; Jeongah Shin; Yumi Cho; Jae Kwon Shin; Kanghyeon Kim; Jeongyun Heo; Qiyue Wang; et al. (Chemical Engineering Journal, 2025)

Exploring flavor patterns in the peel of tangor: A new citrus variety based on electronic sensors and GC–MS/O - Seong Min Jo; Hee Sung Moon; Seong Jun Hong; Sojeong Yoon; Hyangyeon Jeong; Hyeonjin Park; Younglan Ban; Moon Yeon Youn; Youngseung Lee; Sung-Soo Park; Jae Kyeom Kim; Eui-Cheol Shin (Food Chemistry, 2025)

Elucidation of chemosensory and neurophysiological approaches of rice (Oryza sativa L.) bran foods with sugar substitutes through permutation and machine learning-assisted screening methods - Hyeonjin Park; Younglan Ban; Seong Jun Hong; Se Young Yu; Hee Sung Moon; Eui-Cheol Shin (Food Bioscience, 2025)

Estimation of Potentially Toxic Substances and Health Risks in VOCs in Urban Areas of Seoul - Shin-Young Park; Hyeok Jang; Kwang-rae Kim; Hyun-ju Ha; Yuri Choi; Seung-mi Kwon; Yongsuk Choi; Ju-Sung Park; Cheol-Min Lee (Water, Air, & Soil Pollution, 2025)

A multi-platform based metabolic comparison of dill (Anethum graveolens) and fennel (Foeniculum vulgare) using NMR and UPLC–QTOF/MS - Bo-Ram Choi; Dahye Yoon; Woo Cheol Shin; Jin-Kyu Jang; Sookyeong Lee; Dae Young Lee (Journal of Plant Biochemistry and Biotechnology, 2025)
Fennel and dill are well-known aromatic plants and are widely used commercially. They have also been recognized as a medicinal herb with numerous pharmacological activities. Thus, the interest in dill and fennel has been growing, and their industrial use is becoming more important. In this study, seeds of fennel and dill were extracted and analyzed using nuclear magnetic resonance (NMR) spectroscopy and ultra-performance liquid chromatography coupled to quadrupole time-of-flight mass spectrometry (UPLC–QTOF/MS)-based metabolomics. Through 1D and 2D NMR analysis, a total of 34 primary metabolites were identified, and using UPLC–QTOF/MS, different chromatograms of dill and fennel were obtained in less than 20 min. In the multivariate statistical analysis of data obtained from NMR and MS, it was confirmed that seeds of dill and fennel discriminated clearly. Sugars and organic acids were identified as the primary metabolites contributing to significant differentiation of fennel and dill. Also, flavonoids, which were identified as secondary metabolites, significantly differentiated dill and fennel.

Long-acting exendin-4-coated selenium nanoparticles with improved hypoglycemic activity - Reeju Amatya; Amala Joseph; Gu Seob Roh; Kwan Hyung Cho; Cheol Moon; Kyoung Ah Min; Meong Cheol Shin (Journal of Pharmaceutical Investigation, 2025)

Parametric CFD-FEA Study on the Aerodynamic and Structural Performance of NaviScreen for Wind Resistance Reduction in Medium-Sized Commercial Ships - Jin-Man Kim; Jun-Taek Lim; Kwang Cheol Seo; Joo-Shin Park (Journal of Marine Science and Engineering, 2025)
Meeting the International Maritime Organization’s (IMO) 2050 targets for reducing greenhouse gas (GHG) emissions requires cost-effective solutions that minimize wind resistance without compromising safety, particularly for medium-sized multipurpose vessels (MPVs), which have been underrepresented in prior research. This study numerically evaluates 20 bow-mounted NaviScreen configurations using a coupled high-fidelity computational fluid dynamics (CFD) and finite element analysis (FEA) approach. Key design variables—including contact angle (35–50°), lower-edge height (1.2–2.0 m), and horn position (3.2–5.3 m)—were systematically varied. The sloped Type-15 shield reduced aerodynamic resistance by 17.1% in headwinds and 24.5% at a 30° yaw, lowering total hull resistance by up to 8.9%. Nonlinear FEA under combined dead weight, wind loads, and Korean Register (KR) green-water pressure revealed local buckling risks, which were mitigated by adding carling stiffeners and increasing plate thickness from 6 mm to 8 mm. The reinforced design satisfied KR yield limits, ABS buckling factors (>1.0), and NORSOK displacement criteria (L/100), confirming structural robustness. This dual-framework approach demonstrates the viability of NaviScreens as passive aerodynamic devices that enhance fuel efficiency and reduce GHG emissions, aligning with global efforts to address climate change by targeting not only CO2 but also other harmful emissions (e.g., NOx, SOx) regulated under MARPOL. The study delivers a validated CFD-FEA workflow to optimize performance and safety, offering shipbuilders a scalable solution for MPVs and related vessel classes to meet IMO’s GHG reduction goals.

FDA-hydrolysis activity: A pre-screening tool for optimizing compost selection in standardized plastic biodegradation testing - Hyuni Jung; Sohyeon Park; Seul-A Park; Hyeri Kim; Minkyung Lee; Cheol Hun Park; Jonggeon Jegal; Giyoung Shin; Hyo Jeong Kim (Waste Management, 2025)

Antioxidant and chemosensory properties of rice (Oryza sativa L.) bran under different oven-roasting conditions - Hyeonjin Park; Younglan Ban; Seong Jun Hong; Sojeong Yoon; Hee Sung Moon; Se Young Yu; Eui-Cheol Shin (Food Chemistry, 2025)

Sensomics and chemometrics approaches of differential brewed and roasted coffee (Coffea arabica) from Ethiopia using biomimetic sensory-based machine perception techniques: Effects of caffeine on bitter taste and the generation of volatiles - Younglan Ban; Hyeonjin Park; Seong Jun Hong; Se Young Yu; Hee Sung Moon; Eui-Cheol Shin (Food Chemistry, 2025)

Erratum to “Accuracy, generalizability, and extrapolation ability of physics-based, data-driven, and hybrid models for real-life cooling towers” - Jin Hong Kim; Young Sub Kim; Hyeong Gon Jo; Eiji Urabe; Junghyon Mun; Yukyung Shin; Yongsung Park; Cheol Soo Park (Building and Environment, 2025)

Comparison of the effects of rockwool and coir medium on the growth, fruit quality, and productivity of strawberry (Fragaria × ananassa) in greenhouse soilless culture - Cheol Bin An; Jae Seong Lee; Jong Hwa Shin (Horticulture, Environment, and Biotechnology, 2025)

Time-weighted assessment of personal PM2.5 exposure of patients with allergies using portable monitors in Seoul Metropolitan Area, Korea - Hyeok Jang; Shin-Young Park; Cheol-Min Lee (Environmental Monitoring and Assessment, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Sediments near industrial ports can be hotspots of fossil carbon accumulation - Seung-Cheol Lee; Kyung-Hoon Shin; Neung-Hwan Oh (Marine Pollution Bulletin, 2025)

Enhancement of health beneficial bioactivities of bitter melon (Momordica charantia L.) by puffing - Ho-Jin Chung; Jae-Sung Shin; Min-Seok Kim; Soon-Cheol Ahn; Young Ho Koh; Seok Hyun Eom; Moo-Yeol Baik (Food Chemistry, 2025)

Accuracy, generalizability, and extrapolation ability of physics-based, data-driven, and hybrid models for real-life cooling towers - Jin Hong Kim; Young Sub Kim; Hyeong Gon Jo; Eiji Urabe; Junghyon Mun; Yukyung Shin; Yongsung Park; Cheol Soo Park (Building and Environment, 2025)

Investigation of non-volatile and volatile compound profiles in Arabica coffee extracts and neurophysiological effects of different chemosensory stimulation according to sex: Insights from electronic sensors, EEG, and sLORETA approaches - Seong Jun Hong; Sojeong Yoon; Younglan Ban; Hyeonjin Park; Hee Sung Moon; Se Young Yu; Moon Yeon Youn; Daeyong Shin; Kiseong Kim; Young Jun Kim; Jae Kyeom Kim; Eui-Cheol Shin (Food Chemistry, 2025)

PM exposure during pregnancy affects childhood asthma via placental epigenetic changes: Neuronal differentiation and proliferation and Notch signaling pathways - Hyo-Bin Kim; Si Hyeon Lee; Dae Yeol Yang; Seung-Hwa Lee; Jeong-Hyun Kim; Hwan-Cheol Kim; Kil Yong Choi; So-Yeon Lee; Song-I Yang; Dong In Suh; Youn Ho Shin; Kyung Won Kim; et al. (Environmental Pollution, 2025)

Undibacterium cyanobacteriorum sp. nov., an auxin-producing bacterium isolated from fresh water during cyanobacterial bloom period - Ve Van Le; So-Ra Ko; Loan Thi Thanh Nguyen; Jin-Cheol Kim; Yuna Shin; Kyunghyun Kim; Chi-Yong Ahn (Antonie van Leeuwenhoek, 2024)

Spatiotemporal distribution and source analysis of PM2.5 and its chemical components in national industrial complexes of Korea: a case study of Ansan and Siheung - Shin-Young Park; Hyeok Jang; Jaymin Kwon; Yong-Sung Cho; Jung-Il Lee; Cheol-Min Lee (Environmental Science and Pollution Research, 2024)

Characterization of taste and aroma profile in pomegranate (Punica granatum L.) seed oil using electronic sensors, GC-MS/olfactometry - Sojeong Yoon; Hyangyeon Jeong; Seong Jun Hong; Seong Min Jo; Hyunjin Park; Younglan Ban; Moon Yeon Youn; Jae Kyeom Kim; Young Jun Kim; Eui-Cheol Shin (Food Bioscience, 2024)

Elucidating different roles of solvent additives in organic photovoltaics under solar and indoor light emission environments - Gyeong G. Jeon; Jinseck Kim; Hyeong Ju Eun; Jong-Woon Ha; Sein Chung; So Jeong Shin; Kilwon Cho; Sung Cheol Yoon; Bumjoon J. Kim; Seo-Jin Ko; Jong H. Kim (Chemical Engineering Journal, 2024)

Sources of subway PM2.5: Investigation of a system with limited mechanical ventilation - Keith Van Ryswyk; Ryan Kulka; Cheol-Heon Jeong; Angelos T. Anastasopolos; Tim Shin; Peter Blanchard; Danielle Veikle; Greg J. Evans (Transportation Research Part D: Transport and Environment, 2024)

Valorization of battery manufacturing wastewater: Recovery of high-value metal ions through reaction-enhanced membrane cascade - Jeong Han Shin; Seung Hwan Kim; Cheol Hun Yoo; Ho Jun Lee; Bao Tran Duy Nguyen; Go Gi Lee; Jeong F. Kim; Jong Suk Lee (Chemical Engineering Journal, 2024)

Physicochemical and chemosensory properties of pomegranate (Punica granatum L.) seeds under various oven-roasting conditions - Sojeong Yoon; Hyangyeon Jeong; Seong Min Jo; Seong Jun Hong; Hyeonjin Park; Younglan Ban; Moon Yeon Youn; Eui-Cheol Shin (Food Chemistry, 2024)

Performance gap analysis for Korean building energy efficiency certification - Young Seo Yoo; Hansol Shin; Deuk Woo Kim; Cheol Soo Park (Energy and Buildings, 2024)

Degradation of trace pollutants in industrial wastewater using underwater nonthermal plasma: Toward evaluation of bioecotoxicity - Heejae Lee; Yongwook Shin; Kangil Kim; Haekwang Kim; Joonseok Kang; Jewan Yoo; Sung Un Kang; Youngsuk Yoo; Yong Cheol Hong (Chemical Engineering Journal, 2024)

Designing an Atmospheric Monitoring Network to Verify National CO2 Emissions - Sojung Sim; Sujong Jeong; Chaerin Park; Jaewon Shin; Insun Kim; Sujin Ban; Cheol-Soo Lim (Asia-Pacific Journal of Atmospheric Sciences, 2024)

Sedimentary evolution of the Nakdong River deposits on the Korea Strait shelf since the Last Glacial Maximum - Dong-Lim Choi; Byung-Cheol Kum; Dong-Hyeok Shin; Seok Jang (Marine Geology, 2024)

Dithienopyran-based narrow-bandgap donor polymers: Unveiling the potential for semitransparent organic solar cells with enhanced NIR absorption - Seung Un Ryu; Du Hyeon Ryu; Dae Hwan Lee; Zia Ur Rehman; Jong-Cheol Lee; Haeryang Lim; Giwon Shin; Chang Eun Song; Taiho Park (Chemical Engineering Journal, 2024)

Membrane reciprocation and quorum quenching: An innovative combination for fouling control and energy saving in membrane bioreactors - Jinwoo Kim; Eunjin Bae; Hyeona Park; Hyung-June Park; Syed Salman Ali Shah; Kibaek Lee; Jaewoo Lee; Hyun-Suk Oh; Pyung-Kyu Park; Yong Cheol Shin; HeeWan Moon; Vincenzo Naddeo; et al. (Water Research, 2024)

Considering the Chemical Components of Particulate Matter 2.5 for Assessing Its Health Risks to Residents near the Ansan/Siheung and Ulsan Industrial Complexes - Ji-Yun Jung; Shin-Young Park; Jeong-In Jeon; Hye-Won Lee; Sung-Won Yoon; Cheol-Min Lee (Water, Air, & Soil Pollution, 2024)

Correction to: Rapid analysis of insecticidal metabolites from the entomopathogenic fungus Beauveria bassiana 331R using UPLC-Q-Orbitrap MS - Jong-Cheol Kim; In Min Hwang; Ho Myeong Kim; Seulbi Kim; Teak Su Shin; Soo-Dong Woo; Hae Woong Park (Mycotoxin Research, 2024)

Rapid analysis of insecticidal metabolites from the entomopathogenic fungus Beauveria bassiana 331R using UPLC-Q-Orbitrap MS - Jong-Cheol Kim; In Min Hwang; Ho Myeong Kim; Seulbi Kim; Teak Su Shin; Soo-Dong Woo; Hae Woong Park (Mycotoxin Research, 2024)

Achieving highly efficient kesterite solar cells using simultaneous surface Ge substitution and rear interface engineering strategies - Myeong Cheol Baek; Jun Sung Jang; Vijay C. Karade; Mahesh P. Suryawanshi; JunHo Kim; Tae Ei Hong; Sang Woo Park; Seung Wook Shin; Jin Hyeok Kim (Chemical Engineering Journal, 2024)

Facile and rapid fabrication of wearable biosensors via femtosecond laser-directed micro-patterning with large-sized reduced graphene oxide for physiological monitoring - Hae-In Moon; Sungil Kim; Jeong Eun Byun; Young Won Kim; Yeon Wook Jung; Seung Geun Jo; Yujin Shin; Yeoul Kang; Sang Jun Kim; Eun-Su Lee; Hyung-Jong Lee; Min-Cheol Oh; et al. (Chemical Engineering Journal, 2024)

Proliferation-Related Features of the Human Mesenchymal Stem Cells Derived from Palatine Tonsils, Adipose Tissues, and Bone Marrow - Sohee Park; Yeuni Yu; Gi Cheol Park; Sung-Chan Shin; Ji Min Kim; Byung-Joo Lee; Yun Hak Kim (Tissue Engineering and Regenerative Medicine, 2023)

Risk of gastric cancer among long-term proton pump inhibitor users: a population-based cohort study - Jong Wook Kim; Hye-Kyung Jung; Bora Lee; Cheol Min Shin; Eun Jeong Gong; Jitaek Hong; Young Hoon Youn; Kwang Jae Lee (European Journal of Clinical Pharmacology, 2023)

Multiple toll-like receptors (TLRs) display differential bacterial and ligand specificity in the earthworm, Eisenia andrei - Beom Jun Park; Yoo Bin Yoon; Soon Cheol Park; Geun-Seup Shin; Hee-Jin Kwak; Dong Ho Lee; Min Young Choi; Jung-Woong Kim; Sung–Jin Cho (Journal of Invertebrate Pathology, 2023)

Development of high-performance organic photodetectors by understanding origin of dark current density with synthesis of photoconductive polymers - WonJo Jeong; Jinhyeon Kang; Dongchan Lee; Cheol Shin; Hyungju Ahn; Chan So; Jong Ho Won; Dae Sung Chung; Shinuk Cho; In Hwan Jung (Chemical Engineering Journal, 2023)

Therapeutic Effect of HDAC5 Binding and Cell Penetrating Peptide for the Treatment of Inflammatory Bowel Disease - Deogil Kim; Dong Woo Lee; Gookjin Yoon; Eui Kyun Jeong; Moon Sil Choi; Hoo Cheol Lee; Yoon Shin Park; Chong Pyung Chung; Jue-Yeon Lee; Yoon Jeong Park (Tissue Engineering and Regenerative Medicine, 2023)

Functional significance of serine 13 in the active site of glutathione S-transferase F3 from Oryza sativa - Su-Bin Jin; Si-Wook Jang; Ji-Ae Shin; Na-Hee Jung; Hyun-A Kim; Seo-Young Park; Woo-Cheol Lee; Kwang-Hoon Kong (Pesticide Biochemistry and Physiology, 2023)

Environmental DNA surveillance of biocontamination in a drinking water treatment plant - Kyu-Young Shim; Heesang Shin; In-Cheol Yeo; Kyu Ri Kim; Ihn-Sil Kwak; Chang-Bum Jeong (Journal of Hazardous Materials, 2023)

Determination of the origin of surface water in the Saijo Plain, Japan, using antimony as a geochemical tracer - Minoru Tokumasu; Ki-Cheol Shin; Yoshihiro Yamada (Limnology, 2023)

Injectable remodeling hydrogels derived from alendronate-tethered alginate calcium complex for enhanced osteogenesis - Han-Sem Kim; JunHwee Jang; Jun-Sung Oh; Eun-Jung Lee; Cheol-Min Han; Ueon Sang Shin (Carbohydrate Polymers, 2023)

Iron oxide nanoparticles-loaded hydrogels for effective topical photothermal treatment of skin cancer - Reeju Amatya; Doyeon Kim; Kyoung Ah Min; Meong Cheol Shin (Journal of Pharmaceutical Investigation, 2022)

Network-based toxicogenomic approach to explore oral benzo(a)pyrene exposure effect on respiratory system - Su Ji Kim; Dong Yeop Shin; Yujin Jang; Sang Min Lee; Cheol Min Lee; Yeon Soon Ahn; Young Rok Seo (Molecular & Cellular Toxicology, 2022)

Association between smartphone addiction risk, sleep quality, and sleep duration among Korean school-age children: a population-based panel study - Minah Park; Sung Hoon Jeong; Kyungduk Huh; Yu Shin Park; Eun-Cheol Park; Suk-Yong Jang (Sleep and Biological Rhythms, 2022)

A review of glucoregulatory hormones potentially applicable to the treatment of Alzheimer’s disease: mechanism and brain delivery - Reeju Amatya; Kyoung Ah Min; Meong Cheol Shin (Journal of Pharmaceutical Investigation, 2022)

Transcriptional upregulation of multiple earthworm chitinase genes following bacterial challenge suggests their implications in innate immunity - Beom Jun Park; Yoo Bin Yoon; Dong Ho Lee; Chuog Shin; Louis Juakali; Sung-Jin Cho; Soon Cheol Park (Genes & Genomics, 2021)

Dietary supplementations of Bacillus probiotic improve digestibility, growth performance, innate immunity, and water ammonia level for Pacific white shrimp, Litopenaeus vannamei - Chorong Lee; Soohwan Kim; Jaehyeong Shin; Min-Gi Kim; Buddhi E. Gunathilaka; Sung Hun Kim; Ji Eun Kim; Seung-Cheol Ji; Jee Eun Han; Kyeong-Jun Lee (Aquaculture International, 2021)

Correction to: Combined Application of Prototype Ultrasound and BSA-Loaded PLGA Particles for Protein Delivery - Minki Jin; Sung Ho Seo; Bo Seok Kim; Seungmi Hwang; Yun Gyeong Kang; Jung-Woog Shin; Kwan Hyung Cho; Jimi Byeon; Meong Cheol Shin; Doyeon Kim; Changhan Yoon; Kyoung Ah Min (Pharmaceutical Research, 2021)

An Experimental Analysis of Active Pitch Control for an Assault Amphibious Vehicle Considering Waterjet-Hydrofoil Interaction Effect - Daehan Lee; Sanggi Ko; Jongyeol Park; Yong Cheol Kwon; Shin Hyung Rhee; Myungjun Jeon; Tae Hyung Kim (Journal of Marine Science and Engineering, 2021)
The present study aims to reduce the pitch motion of an assault amphibious vehicle system in seaways by waterjet impeller revolution rate control. A series of seakeeping tests were performed in a towing tank with a 1/4.5-scale model. This vehicle is manufactured as a box-shaped hull, and since an appendage that generates lift force is attached, the amount of change in pitch motion is large according to the forward speed. For pitch motion reduction, the impeller revolution rate and resultant pitch moment were controlled through a proportional-integral-derivative controller. Improvements in seakeeping performance were examined in both regular and irregular conditions by the model tests in terms of root mean square of pitch motion. The tuned controller decreased pitch motion by more than 60%.

Combined Application of Prototype Ultrasound and BSA-Loaded PLGA Particles for Protein Delivery - Minki Jin; Sung Ho Seo; Bo Seok Kim; Seungmi Hwang; Yun Gyeong Kang; Jung-Woog Shin; Kwan Hyung Cho; Jimi Byeon; Meong Cheol Shin; Doyeon Kim; Changhan Yoon; Kyoung Ah Min (Pharmaceutical Research, 2021)

BSA/Silver Nanoparticle-Loaded Hydrogel Film for Local Photothermal Treatment of Skin Cancer - Reeju Amatya; Seungmi Hwang; Taehoon Park; Yoon Ju Chung; Sehee Ryu; Jihyeong Lee; Heesun Cheong; Cheol Moon; Kyoung Ah Min; Meong Cheol Shin (Pharmaceutical Research, 2021)

Indole-6-carboxaldehyde prevents oxidative stress-induced mitochondrial dysfunction, DNA damage and apoptosis in C2C12 skeletal myoblasts by regulating the ROS-AMPK signaling pathway - Cheol Park; Hyesook Lee; Shin-Hyung Park; Su Hyun Hong; Kyoung Seob Song; Hee-Jae Cha; Gi-Young Kim; Young-Chae Chang; Suhkmann Kim; Heui-Soo Kim; Yung Hyun Choi (Molecular & Cellular Toxicology, 2020)

Impact of Tropical Initial Water Vapor from MT-SAPHIR Observations on Medium-Range Forecasts Using the KMA Operational Model - Nuri On; Sanghee Jun; Junsu Kim; Hyun-Cheol Shin (Asia-Pacific Journal of Atmospheric Sciences, 2020)

The role of service quality and perceived behavioral control in shared electric bicycle in China: Does residual effects of past behavior matters? - Liang Li; Bangzhu Zhu; Minxing Jiang; Xiang Cai; Antonio K. W. Lau; Geon-Cheol Shin (Environmental Science and Pollution Research, 2020)

Major and trace elements in the surface water of Tonle Sap Lake, Mekong River, and other tributary rivers in Cambodia - Takashi Yoshikawa; Akira P. Takagi; Satoshi Ishikawa; Mina Hori; Takanori Nakano; Ki-Cheol Shin; Hort Sitha; Eng Cheasan; Srun Limsong (Environmental Monitoring and Assessment, 2020)

How Cancer Patients Perceive Clinical Trials (CTs) in the Era of CTs: Current Perception and Its Differences Between Common and Rare Cancers - Ji Hyun Park; Ji Sung Lee; HaYeong Koo; Jeong Eun Kim; Jin-Hee Ahn; Min-Hee Ryu; Sook-ryun Park; Shin-kyo Yoon; Jae Cheol Lee; Yong-Sang Hong; Sun Young Kim; Kyo-Pyo Kim; et al. (Journal of Cancer Education, 2020)

Evaluation of chlorophyll fluorescence parameters and proline content in tomato seedlings grown under different salt stress conditions - Yu Kyeong Shin; Shiva Ram Bhandari; Myeong Cheol Cho; Jun Gu Lee (Horticulture, Environment, and Biotechnology, 2020)

Evaluation of Major Dietary Ingredients in Diverse Oats (Avena sativa L.) Germplasm - Muhammad Rauf; Hyemyeong Yoon; Sukyeung Lee; Myoung-Jae Shin; Ho-Cheol Ko; Myung-Chul Lee; Sejong Oh; Do-Yoon Hyun; Onsook Hur; Yu Mi Choi (Journal of Crop Science and Biotechnology, 2019)

Pleistocene forced regressive deposits on the Korea Strait shelf influenced by tectonic and ocean currents - Dong-Lim Choi; Yong-Kuk Lee; Dong-Hyeok Shin; Seom-Kyu Jung; Byung-Cheol Kum (Geo-Marine Letters, 2019)

Externally Controlled Cellular Transport of Magnetic Iron Oxide Particles with Polysaccharide Surface Coatings - Kwan Hyung Cho; Meong Cheol Shin; Kyoung Ah Min (Cell Biochemistry and Biophysics, 2019)

Fluoro-Jade B histofluorescence staining detects dentate granule cell death after repeated five-minute transient global cerebral ischemia - Ji Hyeon Ahn; Taek Geun Ohk; Dae Won Kim; Hyunjung Kim; Minah Song; Tae-Kyeong Lee; Jae-Chul Lee; Go Eun Yang; Myoung Cheol Shin; Jun Hwi Cho; Soo Young Choi; Moo-Ho Won; et al. (Metabolic Brain Disease, 2019)

Whole genome sequencing analysis of horse populations inhabiting the Korean Peninsula and Przewalski’s horse - Ha-Seung Seong; Nam-Young Kim; Dae Cheol Kim; Nam-Hyun Hwang; Da-Hye Son; Jong Suh Shin; Joon-Hee Lee; Won-Hyong Chung; Jung-Woo Choi (Genes & Genomics, 2019)

Loss of Arabidopsis Halotolerance 2-like (AHL), a 3′-phosphoadenosine-5′-phosphate phosphatase, suppresses insensitive response of Arabidopsis thaliana ring zinc finger 1 (atrzf1) mutant to abiotic stress - Da-Jeong Shin; Ji-Hee Min; Tinh Van Nguyen; Young-Min Kim; Cheol Soo Kim (Plant Molecular Biology, 2019)

Pharmaceutical challenges and perspectives in developing ophthalmic drug formulations - Pooja Maharjan; Kwan Hyung Cho; Anjila Maharjan; Meong Cheol Shin; Cheol Moon; Kyoung Ah Min (Journal of Pharmaceutical Investigation, 2019)

The Effects of Differences in Vegetation on Calcium Dynamics in Headwater Streams - Tamihisa Ohta; Ki-Cheol Shin; Yu Saitoh; Takanori Nakano; Tsutom Hiura (Ecosystems, 2018)

Genome-wide analyses of the Jeju, Thoroughbred, and Jeju crossbred horse populations using the high density SNP array - Nam Young Kim; Ha-Seung Seong; Dae Cheol Kim; Nam Geon Park; Byoung Chul Yang; Jun Kyu Son; Sang Min Shin; Jae Hoon Woo; Moon Cheol Shin; Ji Hyun Yoo; Jung-Woo Choi (Genes & Genomics, 2018)

Cruciferous vegetables and colorectal cancer prevention through microRNA regulation: A review - Jeong Hoon Pan; Breann Abernathy; Young Jun Kim; Jin Hyup Lee; Jun Ho Kim; Eui Cheol Shin; Jae Kyeom Kim (Critical Reviews in Food Science and Nutrition, 2018)

Brain ischemic preconditioning protects against moderate, not severe, transient global cerebral ischemic injury - Jae-Chul Lee; Bich-Na Shin; Jeong Hwi Cho; Tae-Kyeong Lee; In Hye Kim; YooHun Noh; Sung-Su Kim; Hyang-Ah Lee; Young-Myeong Kim; Hyeyoung Kim; Jun Hwi Cho; Joon Ha Park; et al. (Metabolic Brain Disease, 2018)

Effects of waterborne copper on oxidative stress and immune responses in red seabream, Pagrus major - Cheol Young Choi; Jong Ryeol Choe; Yoon Sub Shin; Tae Hwan Kim; Ji Yong Choi; Bong-Seok Kim (Molecular & Cellular Toxicology, 2018)

Late Pleistocene sequence architecture on the geostrophic current-dominated southwest margin of the Ulleung Basin, East Sea - Dong-Lim Choi; Dong-Hyeok Shin; Byung-Cheol Kum; Seok Jang; Jin-Hyung Cho; Hyeong-Tae Jou; Nam-Do Jang (Geo-Marine Letters, 2018)

Molecular and cellular toxicological profiling of DNA bis-intercalator, quinoxaline compounds: echinomycin as the versatile lead - Yoon-Sun Park; Woon-Seob Shin; Cheol-Su Kim; Chan Mug Ahn; Xu-Feng Qi; Soo-Ki Kim (Molecular & Cellular Toxicology, 2018)

Cell-penetrating peptide-based non-invasive topical delivery systems - Tru Van Nguyen; Meong Cheol Shin; Kyoung Ah Min; Yongzhuo Huang; Euichaul Oh; Cheol Moon (Journal of Pharmaceutical Investigation, 2018)

Effect of different wavelengths of light on the antioxidant and immunity status of juvenile rock bream, Oplegnathus fasciatus, exposed to thermal stress - Jong Ryeol Choe; Yoon Sub Shin; Ji Yong Choi; Tae Hwan Kim; Min-Min Jung; Cheol Young Choi (Ocean Science Journal, 2017)

Comparative proteomic analysis of the response of fibrous roots of nematode-resistant and -sensitive sweet potato cultivars to root-knot nematode Meloidogyne incognita - Joon Ha; Jong Chan Won; Yong Hak Jung; Jung-Wook Yang; Hyeong-Un Lee; Ki Jung Nam; Sung-Chul Park; Jae Cheol Jeong; Shin-Woo Lee; Dong Woon Lee; Jung-Sung Chung; Jeung Joo Lee; et al. (Acta Physiologiae Plantarum, 2017)

Entomopathogenic Beauveria bassiana granules to control soil-dwelling stage of western flower thrips, Frankliniella occidentalis (Thysanoptera: Thripidae) - Se Jin Lee; Sihyeon Kim; Jong Cheol Kim; Mi Rong Lee; Muktadir S. Hossain; Taek Su Shin; Tae Hoon Kim; Jae Su Kim (BioControl, 2017)

Twenty-Eight-Day Repeated Inhalation Toxicity Study of Nano-Sized Neodymium Oxide in Male Sprague-Dawley Rats - Yong-Soon Kim; Cheol-Hong Lim; Seo-Ho Shin; Jong-Choon Kim (Toxicological Research, 2017)

Functional characterization of cytochrome P450 monooxygenases in the cereal head blight fungus F usarium graminearum - Ji Young Shin; Duc‐Cuong Bui; Yoonji Lee; Hyejin Nam; Soyun Jung; Miao Fang; Jin‐Cheol Kim; Theresa Lee; Hun Kim; Gyung Ja Choi; Hokyoung Son; Yin‐Won Lee (Environmental Microbiology, 2017)
Summary Fusarium graminearum is a prominent plant pathogenic fungus causing Fusarium head blight in major cereal crops worldwide. To understand the molecular mechanisms underlying fungal development and virulence, large collections of F. graminearum mutants have been constructed. Cytochrome P450 monooxygenases (P450s) are widely distributed in organisms and are involved in a diverse array of molecular/metabolic processes; however, no systematic functional analysis of P450s has been attempted in filamentous fungi. In this study, we constructed a genome‐wide deletion mutant set covering 102 P450s and analyzed these mutants for changes in 38 phenotypic categories, including fungal development, stress responses and responses to several xenobiotics, to build a comprehensive phenotypic dataset. Most P450 mutants showing defective phenotypes were impaired in a single phenotypic trait, demonstrating that our mutant library is a good genetic resource for further fungal genetic studies. In particular, we identified novel P450s specifically involved in virulence (5) and both asexual (1) and sexual development (2). Most P450s seem to play redundant roles in the degradation of xenobiotics in F. graminearum . This study is the first phenome‐based functional analysis of P450s, and it provides a valuable genetic resource for further basic and applied biological research in filamentous fungi and other plant pathogens.

Preparation and Characterization of Gelonin-Melittin Fusion Biotoxin for Synergistically Enhanced Anti-Tumor Activity - Meong Cheol Shin; Kyoung Ah Min; Heesun Cheong; Cheol Moon; Yongzhuo Huang; Huining He; Victor C. Yang (Pharmaceutical Research, 2016)

Toluene induces early growth response-1 dependent thymic stromal lymphopoietin expression in human keratinocytes - Hana Lee; Jae Beom Park; Hyu Cheol Bae; Woo-In Ryu; Jung Jin Shin; Sang Wook Son (Molecular & Cellular Toxicology, 2016)

Estimation of the flow resistances exerted in coronary arteries using a vessel length-based method - Kyung Eun Lee; Soon-Sung Kwon; Yoon Cheol Ji; Eun-Seok Shin; Jin-Ho Choi; Sung Joon Kim; Eun Bo Shim (Pflügers Archiv - European Journal of Physiology, 2016)

Human Airway Primary Epithelial Cells Show Distinct Architectures on Membrane Supports Under Different Culture Conditions - Kyoung Ah Min; Gus R. Rosania; Meong Cheol Shin (Cell Biochemistry and Biophysics, 2016)

Functional characteristics of the natural polymorphisms of HIV-1 gp41 in HIV-1 isolates from enfuvirtide-naïve Korean patients - YoungHyun Shin; Cheol-Hee Yoon; Hyo-Jin Yang; Hoyong Lim; Byeong-Sun Choi; Sung Soon Kim; Chun Kang (Archives of Virology, 2016)

Is there a relationship between PPARD T294C/PPARGC1A Gly482Ser variations and physical endurance performance in the Korean population? - Han-Jun Jin; In-Wook Hwang; Ki-Cheol Kim; Hyun-Ik Cho; Tae-Hwan Park; Yun-A Shin; Ho-Seong Lee; Ji-Hyun Hwang; Ah-Ram Kim; Kwang-Hee Lee; Ye-Eun Shin; Ji-Yeon Lee; et al. (Genes & Genomics, 2016)

Variation in summer surface air temperature over Northeast Asia and its associated circulation anomalies - Wei Chen; Xiaowei Hong; Riyu Lu; Aifen Jin; Shizhu Jin; Jae-Cheol Nam; Jin-Ho Shin; Tae-Young Goo; Baek-Jo Kim (Advances in Atmospheric Sciences, 2016)

Cucurbitacin D induces cell cycle arrest and apoptosis by inhibiting STAT3 and NF-κB signaling in doxorubicin-resistant human breast carcinoma (MCF7/ADR) cells - Jin Mo Ku; Soon Re Kim; Se Hyang Hong; Han-Seok Choi; Hye Sook Seo; Yong Cheol Shin; Seong-Gyu Ko (Molecular and Cellular Biochemistry, 2015)

Betacellulin ameliorates hyperglycemia in obese diabetic db/db mice - Yoon Sin Oh; Seungjin Shin; Hui Ying Li; Eun-Young Park; Song Mi Lee; Cheol Soo Choi; Yong Lim; Hye Seung Jung; Hee-Sook Jun (Journal of Molecular Medicine, 2015)

Compositions of fatty acids and phytosterols of plant-based oils and their associations with anti-oxidative capacity: Application of principal component analysis - Jae Kyeom Kim; Ho-Jeong Lim; Dong-Hoon Shin; Cho Rong Kim; Mi-Jeong Kim; Jiyeon Chun; Eui-Cheol Shin (Horticulture, Environment, and Biotechnology, 2015)

Age-related change in γH2AX of Drosophila muscle: its significance as a marker for muscle damage and longevity - Ho-Jun Jeon; Young-Shin Kim; Joung-Sun Park; Jung-Hoon Pyo; Hyun-Jin Na; In-Joo Kim; Cheol-Min Kim; Hae Young Chung; Nam Deuk Kim; Robert Arking; Mi-Ae Yoo (Biogerontology, 2015)

Cloning metallothionein gene in Zacco platypus and its potential as an exposure biomarker against cadmium - Sangwoo Lee; Cheolmin Kim; Jungkon Kim; Woo-Keun Kim; Hyun Suk Shin; Eun-Suk Lim; Jin Wuk Lee; Sunmi Kim; Ki-Tae Kim; Sung-Kyu Lee; Cheol Young Choi; Kyungho Choi (Environmental Monitoring and Assessment, 2015)

Heterologous expression of the Brassica rapa transcription factor BrWRKY7 enhances resistance against bacterial soft rot caused by Pectobacterium carotovorum in Arabidopsis - Yu Jin Ko; Seokhyun Lee; Kyungyoung Song; Sang-Yeol Park; Ilpyung Ahn; Shin-cheol Bae; Yeon Hee Lee; Duk-Ju Hwang (Plant Biotechnology Reports, 2015)

Bioactive injectables based on calcium phosphates for hard tissues: A recent update - Roman A. Perez; Song-Hee Shin; Cheol-Min Han; Hae-Won Kim (Tissue Engineering and Regenerative Medicine, 2015)

A pilot study of indoor air quality in screen golf courses - Sun-Ju Nam Goung; Jinho Yang; Yoon Shin Kim; Cheol Min Lee (Environmental Science and Pollution Research, 2015)

Human exposure and risk assessment of cadmium for residents of abandoned metal mine areas in Korea - Jiyeon Yang; Eung-Cheol Kim; Dong-Chun Shin; Seong-Joon Jo; Young-Wook Lim (Environmental Geochemistry and Health, 2015)

Expression of CYP3A in chronic ethanol-fed mice is mediated by endogenous pregnane X receptor ligands formed by enhanced cholesterol metabolism - Young-Tae Je; Woo-Cheol Sim; Dong-Gwang Kim; Byung-Hwa Jung; Ho-Sang Shin; Byung-Hoon Lee (Archives of Toxicology, 2015)

PTD-Modified ATTEMPTS for Enhanced Toxin-based Cancer Therapy: An In Vivo Proof-of-Concept Study - Meong Cheol Shin; Jian Zhang; Kyoung Ah Min; Huining He; Allan E. David; Yongzhuo Huang; Victor C. Yang (Pharmaceutical Research, 2015)

Peptoniphilus mikwangii sp. nov., Isolated from a Clinical Specimen of Human Origin - Eugene Cho; Soon-Nang Park; Yeseul Shin; Yun Kyong Lim; Jayoung Paek; Hak Kyun Kim; Cheol Ho Hwang; Eojin Jo; Dongchun Jin; Young-Hyo Chang; Joong-Ki Kook (Current Microbiology, 2015)

Fusobacterium hwasookii sp. nov., Isolated from a Human Periodontitis Lesion - Eugene Cho; Soon-Nang Park; Yun Kyong Lim; Yeseul Shin; Jayoung Paek; Cheol Ho Hwang; Young-Hyo Chang; Joong-Ki Kook (Current Microbiology, 2015)

Adipose tissue-derived mesenchymal stem cells cultured at high cell density express brain-derived neurotrophic factor and exert neuroprotective effects in a 6-hydroxydopamine rat model of Parkinson’s disease - Joon Beom Park; Jin Suk Lee; Byung Pil Cho; Ki-Jong Rhee; Soon Koo Baik; Jiye Kim; Seong Joon Kang; Dong-Joon Park; Ji-Eun Oh; Ha Cheol Shin; Yong Man Kim; Hyun Soo Kim; et al. (Genes & Genomics, 2015)

Geochemical prospecting for rare earth elements using termite mound materials - Yu Horiuchi; Tetsuji Ohno; Mihoko Hoshino; Ki-Cheol Shin; Hiroyasu Murakami; Maiko Tsunematsu; Yasushi Watanabe (Mineralium Deposita, 2014)

Vegetation abundance on the Barton Peninsula, Antarctica: estimation from high-resolution satellite images - Jung-Il Shin; Hyun-Cheol Kim; Sang-Il Kim; Soon Gyu Hong (Polar Biology, 2014)

Comparative transcriptomic analysis to identify differentially expressed genes in fat tissue of adult Berkshire and Jeju Native Pig using RNA-seq - Simrinder Singh Sodhi; Won Cheoul Park; Mrinmoy Ghosh; Jin Nam Kim; Neelesh Sharma; Kwang Yun Shin; In Cheol Cho; Youn Chul Ryu; Sung Jong Oh; Sung Hoon Kim; Ki-Duk Song; Sang Pyo Hong; et al. (Molecular Biology Reports, 2014)

Up-regulation of the arginine vasotocin precursor gene from Paralichthys olivaceus: isolation and expression upon acute pathogen invasion - Seongdo Lee; Bongsoo Lim; Jehee Lee; Yu-Cheol Kim; Hyowon Kim; Thanthrige Thiunuwan Priyathilaka; W. D. Niroshana Wickramaarachchi; Se-Jae Kim; Shin-Kwon Kim; Hyung-Bok Jeong (Genes & Genomics, 2014)

Polymorphisms of methylenetetrahydrofolate reductase and glutathione S-transferase are not associated with the risk of papillary thyroid cancer in Korean population - Sun-Seog Kweon; Min-Ho Shin; Hee-Nam Kim; Soo-Hyun Kim; Ho-Cheol Kang (Molecular Biology Reports, 2014)

Effects of recombinant growth hormone on growth factor and immune component levels in the cinnamon clownfish, Amphiprion melanopus - Na Na Kim; Hyun Suk Shin; Jehee Lee; Cheol Young Choi (Marine Biology Research, 2014)

Double injection events of mafic magma into supersolidus Yucheon granites to produce two types of mafic enclaves in the Cretaceous Gyeongsang Basin, SE Korea - Jong-Sun Kim; Moon Son; Byoung-Hoon Hwang; Ki-Cheol Shin; Hyeongseong Cho; Young Kwan Sohn (Mineralogy and Petrology, 2014)

Magnetic Targeting of Novel Heparinized Iron Oxide Nanoparticles Evaluated in a 9L-glioma Mouse Model - Jian Zhang; Meong Cheol Shin; Victor C. Yang (Pharmaceutical Research, 2014)

The effect of LED light spectra on antioxidant system by thermal stress in goldfish, Carassius auratus - Na Na Kim; Young Jae Choi; Hyun Suk Shin; Jee Rey Lim; Jeong Min Han; Ji Hyung Cho; Jehee Lee; Gyung-Suk Kil; Cheol Young Choi (Molecular & Cellular Toxicology, 2014)

The stimulatory effect of LED light spectra on genes related to photoreceptors and skin pigmentation in goldfish (Carassius auratus) - Hyun Suk Shin; Cheol Young Choi (Fish Physiology and Biochemistry, 2014)

Distribution features of biological hazardous pollutants in residential environments in Korea - Cheol Min Lee; Soo Jong Hong; Yoon Shin Kim; Gee Yong Park; Sun Ju Nam Goung; Kyung Hwan Kim (Environmental Science and Pollution Research, 2014)

Effects of exogenous cortisol and seawater adaptation on thyroid hormone receptors in the smolt stage of the sockeye salmon, Oncorhynchus nerka - Hyun Suk Shin; Young Jae Choi; Na Na Kim; Jehee Lee; Hiroshi Ueda; Cheol Young Choi (Ichthyological Research, 2014)

Complete genome sequence of marine bacterium Pseudoalteromonas phenolica bacteriophage TW1 - Hakdong Shin; Ju-Hoon Lee; Chi Sang Ahn; Sangryeol Ryu; Byung Cheol Cho (Archives of Virology, 2014)

Effects of waterborne selenium exposure on the antioxidant and immunological activity in the goldfish, Carassius auratus - Young Jae Choi; Na Na Kim; Hyun Suk Shin; Mi Seon Park; Gyung-Suk Kil; Cheol Young Choi (Molecular & Cellular Toxicology, 2013)

CryIIIA toxin gene expression in transgenic rice confers resistance to rice water weevil - Jin-Hyoung Lee; Kong-Sik Shin; Seok-Cheol Suh; Seong-Lyul Rhim; Yeon-Hee Lee; Myung-Ho Lim; Hee-Jong Woo; Yang Qin; Hyun-Suk Cho (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Silibinin inhibits the production of pro-inflammatory cytokines through inhibition of NF-κB signaling pathway in HMC-1 human mast cells - Beom-Rak Kim; Hye-Sook Seo; Jin-Mo Ku; Gyung-Jun Kim; Chan Yong Jeon; Jong Hyeong Park; Bo-Hyoung Jang; Sun-Ju Park; Yong-Cheol Shin; Seong-Gyu Ko (Inflammation Research, 2013)

Normative data for neuromuscular assessment of the hand–arm vibration syndrome and its retrospective applications in Korean male workers - Ryeok Ahn; Cheol-In Yoo; Hun Lee; Chang-Sun Sim; Joo Hyun Sung; Jae-Kook Yoon; Song-Woo Shin (International Archives of Occupational and Environmental Health, 2013)

The effect of various wavelengths of light from light-emitting diodes on the antioxidant system of marine cyanobacteria, Synechococcus sp. - Cheol Young Choi; Na Na Kim; Hyun Suk Shin; Heum Gi Park; Sang-Gyu Cheon; Gyung-Suk Kil (Molecular & Cellular Toxicology, 2013)

Production of 10-hydroxy-12,15(Z,Z)-octadecadienoic acid from α-linolenic acid by permeabilized cells of recombinant Escherichia coli expressing the oleate hydratase gene of Stenotrophomonas maltophilia - Hye-Jin Oh; Kyung-Cheol Shin; Deok-Kun Oh (Biotechnology Letters, 2013)

Over-expression of rice leucine-rich repeat protein results in activation of defense response, thereby enhancing resistance to bacterial soft rot in Chinese cabbage - Young Ho Park; Changhyun Choi; Eun Mi Park; Hyo Sun Kim; Hong Jae Park; Shin Cheol Bae; Ilpyung Ahn; Min Gab Kim; Sang Ryeol Park; Duk-Ju Hwang (Plant Cell Reports, 2012)

Erratum to: Apigenin induces apoptosis via extrinsic pathway, inducing p53 and inhibiting STAT3 and NFκB signaling in HER2-overexpressing breast cancer cells - Hye-Sook Seo; Han-Seok Choi; Soon-Re Kim; Youn Kyung Choi; Sang-Mi Woo; Incheol Shin; Jong-Kyu Woo; Sang-Yoon Park; Yong Cheol Shin; Seong-Gyu Ko (Molecular and Cellular Biochemistry, 2012)

Porcine SPP1 gene polymorphism association with phenotypic traits in the Landrace × Jeju (Korea) black pig F2 population - Sang-Hyun Han; Kwang-Yun Shin; Sung-Soo Lee; Moon-Suck Ko; Hong-Shik Oh; In-Cheol Cho (Molecular Biology Reports, 2012)

Apigenin induces apoptosis via extrinsic pathway, inducing p53 and inhibiting STAT3 and NFκB signaling in HER2-overexpressing breast cancer cells - Hye-Sook Seo; Han-Seok Choi; Soon-Re Kim; Youn Kyung Choi; Sang-Mi Woo; Incheol Shin; Jong-Kyu Woo; Sang-Yoon Park; Yong Cheol Shin; Seong-Kyu Ko (Molecular and Cellular Biochemistry, 2012)

Preparation and in vivo evaluation of immediate-release pellet containing celecoxib solid dispersion - Chun-Woong Park; Nguyen-Thach Tung; Dao-Danh Son; Ju-Young Kim; Yun-Seok Rhee; Seung-Yeop Kang; Shin-Ae Park; Kyu-Mok Hwang; Tack-Oon Oh; Jung-Myung Ha; Sang-Cheol Chi; Eun-Seok Park (Journal of Pharmaceutical Investigation, 2012)

Effects of LED light spectra on the growth of the yellowtail clownfish Amphiprion clarkii - Hyun Suk Shin; Jehee Lee; Cheol Young Choi (Fisheries Science, 2012)

Induction of Fas-mediated extrinsic apoptosis, p21WAF1-related G2/M cell cycle arrest and ROS generation by costunolide in estrogen receptor-negative breast cancer cells, MDA-MB-231 - Youn Kyung Choi; Hye Sook Seo; Han Seok Choi; Hyeong Sim Choi; Soon Re Kim; Yong Cheol Shin; Seong-Gyu Ko (Molecular and Cellular Biochemistry, 2012)

Characterization of Imcrop, a Mutator-like MITE family in the rice genome - Young-Jun Mo; Ki-Young Kim; Woon-Chul Shin; Gun-Mi Lee; Jong-Cheol Ko; Jeong-Kwon Nam; Bo-Kyeong Kim; Jae-Kwon Ko; Yeisoo Yu; Tae-Jin Yang (Genes & Genomics, 2012)

Compositional comparative analysis between insect-resistant rice (Oryza sativa L.) with a synthetic cry1Ac gene and its non-transgenic counterpart - Soo-Yun Park; Si Myung Lee; Jin-Hyoung Lee; Hyeon-Seok Ko; Soon Jong Kweon; Seok-Cheol Suh; Kong-Sik Shin; Jae Kwang Kim (Plant Biotechnology Reports, 2012)

In vitro culture responses of Cratoneuron decipiens (Brid.) G. Roth gametophyte for micropropagation - Md. Giush Uddin Ahmed; So Lim Shin; Cheol Hee Lee (Horticulture, Environment, and Biotechnology, 2011)

An Expressed Sequence Tag Analysis for the Fast-Growing Shoots of Bambusa edulis Murno - Eunjeong Cho; Yurry Um; Seung Kwan Yoo; Hyoungseok Lee; Ho Bang Kim; Serry Koh; Hyun Cheol Shin; Yi Lee (Journal of Plant Biology, 2011)

Cosmogenic 10Be and OSL dating of fluvial strath terraces along the Osip-cheon River, Korea: tectonic implications - Soo Yong Lee; Yeong Bae Seong; Young-Kyu Shin; Kwang Hee Choi; Hee-Cheol Kang; Jeong-Heon Choi (Geosciences Journal, 2011)

Hydraulic Significance of Fractured Zones in Subsea Tunnels - Jong-Ho Shin; Kyu-Cheol Choi; Jae-Ung Yoon; Young-Jin Shin (Marine Georesources & Geotechnology, 2011)

Monitoring of Na+/K+-ATPase mRNA expression in the cinnamon clownfish, Amphiprion melanopus, exposed to an osmotic stress environment: profiles on the effects of exogenous hormone - Mi Seon Park; Hyun Suk Shin; Gyung-Suk Kil; Jehee Lee; Cheol Young Choi (Ichthyological Research, 2011)

Design and efficient production of bovine enterokinase light chain with higher specificity in E. coli - Haarin Chun; Keehyoung Joo; Jooyoung Lee; Hang-Cheol Shin (Biotechnology Letters, 2011)

Pattern Classification of Volatile Organic Compounds in Various Indoor Environments - Cheol Min Lee; Yoon Shin Kim; P. C. Nagajyoti; Whame Park; Ki Youn Kim (Water, Air, & Soil Pollution, 2011)

Influence of quercetin on the physiological response to cadmium stress in olive flounder, Paralichthys olivaceus: effects on hematological and biochemical parameters - Mi Seon Park; Hyun Suk Shin; Jehee Lee; Gyung-Suk Kil; Cheol Young Choi (Molecular & Cellular Toxicology, 2010)

Exogenous Glutamate Inhibits the Root Growth and Increases the Glutamine Content in Arabidopsis thaliana - Ta Hee Kim; Eui Cheol Kim; Suk Weon Kim; Hyo Shin Lee; Dong-Woog Choi (Journal of Plant Biology, 2010)

SINE indel polymorphism of AGL gene and association with growth and carcass traits in Landrace × Jeju black pig F2 population - Sang-Hyun Han; Kwang-Yun Shin; Sung-Soo Lee; Moon-Suck Ko; Dong Kee Jeong; Hong-Shik Oh; Byoung-Chul Yang; In-Cheol Cho (Molecular Biology Reports, 2010)

Molecular characterization of lepidopteran pest-resistant transgenic rice events expressing synthetic Cry1Ac - Kyeong-Ryeol Lee; Kong Sik Shin; Seok Cheol Suh; Ki Young Kim; Yong Hee Jeon; Beom Seok Park; Ju-Kon Kim; Soon-Jong Kweon; Yeon-Hee Lee (Plant Biotechnology Reports, 2009)

Chloroplast-targeted expression of synthetic cry1Ac in transgenic rice as an alternative strategy for increased pest protection - Eun Hye Kim; Seok Cheol Suh; Beom Seok Park; Kong Sik Shin; Soon Jong Kweon; Eun Jung Han; Su-Hyun Park; Youn Shic Kim; Ju-Kon Kim (Planta, 2009)

Depressive symptoms and self-reported occupational injury in small and medium-sized companies - Hwan-Cheol Kim; Shin-Goo Park; Kyoung-Bok Min; Ki-Jung Yoon (International Archives of Occupational and Environmental Health, 2009)

Job stress and depressive symptoms among Korean employees: the effects of culture on work - Shin-Goo Park; Kyoung-Bok Min; Sei-Jin Chang; Hwan-Cheol Kim; Jin-Young Min (International Archives of Occupational and Environmental Health, 2009)

Expression Profiles of Genes Involved in the Carotenoid Biosynthetic Pathway in Yellow-Fleshed Potato Cultivars (Solanum tuberosum L.) from South Korea - Young-Min Goo; Tae-Won Kim; Sun-Hwa Ha; Kyoung-Whan Back; Jung-Myung Bae; Yong-Wook Shin; Cheol-Ho Lee; Mi-Jeong Ahn; Shin-Woo Lee (Journal of Plant Biology, 2009)

Changes of cytochrome P4501A mRNA expression and physiology responses in the olive flounder, Paralichthys olivaceus, exposed to benzo[a]pyrene - Cheol Young Choi†; Kwang Wook An†; Hyun Suk Shin; Myung In An; Pil Gue Jo (Marine Biology Research, 2008)

Expressional characterization of dehydroascorbate reductase cDNA in transgenic potato plants - Young-Min Goo; Hyun Jin Chun; Tae-Won Kim; Cheol-Ho Lee; Mi-Jeong Ahn; Shin-Chul Bae; Kang-Jin Cho; Jae-An Chun; Chung-Han Chung; Shin-Woo Lee (Journal of Plant Biology, 2008)

Identification and characterization of highly expressed genes in suspension-cultured cells of sweet potato - Young Hwa Kim; Cheol Goo Hur; Yun Hee Shin; Jung Myung Bae; Young Sun Song; Gyung Hye Huh (Journal of Plant Biology, 2006)

Accumulation of sweet protein monellin is regulated by thepsbA 5′UTR in tobacco chloroplasts - Kyung Hee Roh; Kong-Sik Shin; Yeon-Hee Lee; Seok-Cheol Seo; Hyo-Guen Park; Henry Daniell; Seung-Bum Lee (Journal of Plant Biology, 2006)

Mutational analysis of human tumor necrosis factor-? - Hang-Cheol Shin; Kwang-Hwi Cho (Biotechnology Letters, 2005)

High level production of bovine angiogenin in E. coli by an efficient refolding procedure - Seung-Hwan Jang; Dong-Ku Kang; Soo-Ik Chang; Harold A. Scheraga; Hang-Cheol Shin (Biotechnology Letters, 2004)

Note: A PCR-Based Analysis of Hox Genes in an Earthworm, Eisenia andrei (Annelida: Oligochaeta) - Pyo Yun Cho; Sung Jin Cho; Myung Sik Lee; Jong Ae Lee; Eun Sik Tak; Chuog Shin; Jong Kil Choo; Soon Cheol Park; Kyu-Seok Lee; Ho-Yong Park; Chang-Bae Kim (Biochemical Genetics, 2004)

Petrographical study on the Yucheon granite and its enclaves - Jong Sun Kim; Ki Cheol Shin; Joon Dong Lee (Geosciences Journal, 2002)

Stage-related chondrogenic potential of human limb bud mesenchyme cells, In vitro: Role of protein kinase C - Yoon-Ah Kook; Chang-Duk Jun; Sung-Gak Hong; Joseph Zernik; Eun-Cheol Kim; Sang-Cheol Kim; Shin-Sung Kang; Hun-Taeg Chung (In Vitro Cellular & Developmental Biology - Animal, 1998)

Cecropin A-melittin hybrid peptide exerts its antifungal effects by damaging on the plasma membranes of Trichosporon beigelii - Dong Gun Lee; Song Yub Shin; Cheol-Young Maeng; Kyung-Soo Hahm (Biotechnology Letters, 1998)

Supply of the argU gene product allows high-level expression of recombinant human interferon-a2a in Escherichia coli - Woojin Jeong; Hang-Cheol Shin (Biotechnology Letters, 1998)

Bacterial chaperones increase the production of soluble human TNF-alpha in Escherichia coli - Woojin Jeong; Nam-Kyu Shin; Hang-Cheol Shin (Biotechnology Letters, 1997)